THE INFLUENCE OF BRAND, SALES PROMOTION AND LOCATION ON INTEREST IN BUYING COFFEE AT KOPI KENANGAN (CASE STUDY ON UNPRI STUDENTS CLASS OF 2021) - Felicia, Evelyn; Jocelyn, Jocelyn; Kok, Selvina; Ginting, Nurmaidah; Lubis, Hana Salsabila (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
Kopi Kenangan has developed into the fastest growing food and beverage retailer in Indonesia. Quantitative as the method used and in this study, convenience sampling technique was used to collect 97 respondents. Data collection methods, including questionnaires, interviews, and documentation and multiple linear regression analysis as data analysis. The results of the hypothesis calculation illustrate Brand, sales promotion has an effect on buying interest both partially and simultaneously